Development of a chatbot with artificial intelligence support for application in a supply chain operational sector - Oliveira, Julya Estevão de; Souza, Noele Bissoli Perini de (Brazilian Journal of Production Engineering, 2026)
Digital transformation has driven efficiency across the supply chain; however, operational sectors still face challenges related to rapid access to information, reliance on tacit knowledge, and difficulty in standardizing internal guidelines. This study analyzed the implementation of an Artificial Intelligence (AI)-based chatbot as an internal support tool in a multinational company, focusing on optimizing the workflow of an area within Supply Chain. This applied case study was structured through document analysis, development of the chatbot on a corporate platform with an LLM, supervised curation and training, and finally, evaluation of user perception. The results indicated a significant improvement in chatbot accuracy, increasing from 65% to 92% between January and September 2025, in addition to 100% approval among direct users. Employees reported greater autonomy, reduced need to interrupt colleagues for clarifications, and improved operational flow. It is concluded that AI, when properly trained and supported by rigorous human curation, is a viable and effective solution to strengthen internal processes, centralize information, and enhance the efficiency of reverse logistics operations.